Cirurgia bariátrica: como e por que suplementar - Bordalo, Livia Azevedo; Teixeira, Tatiana Fiche Sales; Bressan, Josefina; Mourão, Denise Machado (Revista da Associação Médica Brasileira, 2010)
Patients undergoing bariatric surgery are at increased risk of developing nutritional deficiencies from the limited intake and absorption of different nutrients. Thus, a systematic review on PubMed and ISI Web of Science was conducted, including articles from September 1983 to April 2010, to identify literature regarding nutritional deficiencies following bariatric surgery and how treatment is carried out. The keywords used individually or in combinations were: bariatric surgery, obesity, vitamin/mineral deficiencies, protein deficiency, nutrient absorption, and nutrient supplementation. The literature suggests the use of nutritional supplementation to prevent or treat nutritional deficiencies resulting from anatomical changes due to surgical techniques. The success of oral nutritional supplementation in correcting or preventing nutritional deficiencies depends on several factors. Thus, it is very important in clinical practice to understand how the nutrients can be administered. This review aims is to assist in better selecting the nutrients to ensure an appropriate nutrient replacement in patients undergoing bariatric surgery.

Pacientes submetidos à cirurgia bariátrica apresentam maior risco de desenvolver deficiências nutricionais pela limitação na ingestão e absorção de diferentes nutrientes. Desta forma, realizamos uma revisão sistemática no PubMed e ISI Web of Science incluindo artigos de setembro de 1983 a abril de 2010 para identificar as principais deficiências nutricionais após a cirurgia bariátrica e de que forma ocorre o seu tratamento. As palavras-chave utilizadas individualmente ou em associação foram: cirurgia bariátrica, obesidade, deficiência de vitamina/mineral, deficiência de proteína, absorção de nutrientes e suplementação de nutrientes. A literatura sugere que para prevenir ou tratar as deficiências nutricionais decorrentes das alterações anatômicas provocadas pelas técnicas cirúrgicas é necessário o uso de suplementação nutricional. O sucesso da suplementação nutricional oral em corrigir ou prevenir as deficiências nutricionais depende de vários fatores. Assim, compreender as formas pelas quais os nutrientes podem ser administrados é muito importante na prática clínica. Essa revisão tem como objetivo auxiliar a melhor seleção de nutrientes de forma a garantir uma reposição adequada dos nutrientes em pacientes submetidos à cirurgia bariátrica.
Keywords: Nutritional deficiencies; Bariatric surgery; Gastric bypass; Dietary supplements